Pengaruh Pengalaman Dan Kemampuan Kerja Terhadap Kinerja Karyawan Di Balai Latihan Dan Pemberdayaan Masyarakat Desa Daerah Tertinggal dan Transmigrasi Makassar - Nurmega Nurmega (STIM-LPI Makassar, 2022)
This study aims to determine the effect of work experience and work ability on employee performance at BPPMDDTT Makassar. This study uses a combined approach, namely using qualitative and quantitative approaches using primary data as a reference. The sample used in this study is the entire population, which is 60 respondents. This data collection technique uses a questionnaire consisting of 15 statements of the total number. The data analysis technique uses multiple linear regression techniques with simultaneous hypothesis testing (F test), partial test (t test) and coefficient of determination. The results of this study indicate that by means of a simultaneous test (f test) there is a sig probability of 0.000. Sig value < 0.05 (0.000 < 0.05) it can be concluded that Ho is rejected H1 is accepted, so there is a positive and significant influence. Partially (t test) there is an effect of the tcount (3,875) > ttable (1,296) and the resulting significant value is 0.000 which is smaller than 0.05, so Ho is rejected and H1 is accepted.